An efficient face recognition model using multiple angular images and deep neural network architecture - Subah, Silma; Nath, Arpita; Armisha, Mitheela das; Binte Sakhawat, Sumaiya; Alam Parbo, Md Nuhas (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.